Environment and shipping drive environmental DNA beta‐diversity among commercial ports - Jose Andrés; Paul Czechowski; Erin Grey; Mandana Saebi; Kara Andres; Christopher Brown; Nitesh Chawla; James J. Corbett; Rein Brys; Phillip Cassey; Nancy Correa; Marty R. Deveney; et al. (Molecular Ecology, 2023)
The spread of nonindigenous species by shipping is a large and growing global problem that harms coastal ecosystems and economies and may blur coastal biogeographical patterns. This study coupled eukaryotic environmental DNA (eDNA) metabarcoding with dissimilarity regression to test the hypothesis that ship‐borne species spread homogenizes port communities. We first collected and metabarcoded water samples from ports in Europe, Asia, Australia and the Americas. We then calculated community dissimilarities between port pairs and tested for effects of environmental dissimilarity, biogeographical region and four alternative measures of ship‐borne species transport risk. We predicted that higher shipping between ports would decrease community dissimilarity, that the effect of shipping would be small compared to that of environment dissimilarity and shared biogeography, and that more complex shipping risk metrics (which account for ballast water and stepping‐stone spread) would perform better. Consistent with our hypotheses, community dissimilarities increased significantly with environmental dissimilarity and, to a lesser extent, decreased with ship‐borne species transport risks, particularly if the ports had similar environments and stepping‐stone risks were considered. Unexpectedly, we found no clear effect of shared biogeography, and that risk metrics incorporating estimates of ballast discharge did not offer more explanatory power than simpler traffic‐based risks. Overall, we found that shipping homogenizes eukaryotic communities between ports in predictable ways, which could inform improvements in invasive species policy and management. We demonstrated the usefulness of eDNA metabarcoding and dissimilarity regression for disentangling the drivers of large‐scale biodiversity patterns. We conclude by outlining logistical considerations and recommendations for future studies using this approach.

The road not taken: Evolution of tetrodotoxin resistance in the Sierra garter snake ( Thamnophis couchii ) by a path less travelled - Jessica S. Reimche; Robert E. del Carlo; Edmund D. Brodie; Joel W. McGlothlin; Karen Schlauch; Michael E. Pfrender; Edmund D. Brodie; Normand Leblanc; Chris R. Feldman (Molecular Ecology, 2022)
The repeated evolution of tetrodotoxin (TTX) resistance provides a model for testing hypotheses about the mechanisms of convergent evolution. This poison is broadly employed as a potent antipredator defence, blocking voltage‐gated sodium channels (Na v ) in muscles and nerves, paralysing and sometimes killing predators. Resistance in taxa bearing this neurotoxin and a few predators appears to come from convergent replacements in specific Na v residues that interact with TTX. This stereotyped genetic response suggests molecular and phenotypic evolution may be constrained and predictable. Here, we investigate the extent of mechanistic convergence in garter snakes ( Thamnophis ) that prey on TTX‐bearing newts ( Taricha ) by examining the physiological and genetic basis of TTX resistance in the Sierra garter snake ( Th. couchii ). We characterize variation in this predatory adaptation across populations at several biological scales: whole‐animal TTX resistance; skeletal muscle resistance; functional genetic variation in three Na v encoding loci; and levels of gene expression for one of these loci. We found Th. couchii possess extensive geographical variation in resistance at the whole‐animal and skeletal muscle levels. As in other Thamnophis , resistance at both levels is highly correlated, suggesting convergence across the biological levels linking organism to organ. However, Th. couchii shows no functional variation in Na v loci among populations or difference in candidate gene expression. Local variation in TTX resistance in Th. couchii cannot be explained by the same relationship between genotype and phenotype seen in other taxa. Thus, historical contingencies may lead different species of Thamnophis down alternative routes to local adaptation.

Early transcriptional response pathways in Daphnia magna are coordinated in networks of crustacean‐specific genes - Luisa Orsini; James B. Brown; Omid Shams Solari; Dong Li; Shan He; Ram Podicheti; Marcus H. Stoiber; Katina I. Spanier; Donald Gilbert; Mieke Jansen; Douglas B. Rusch; Michael E. Pfrender; et al. (Molecular Ecology, 2018)
Natural habitats are exposed to an increasing number of environmental stressors that cause important ecological consequences. However, the multifarious nature of environmental change, the strength and the relative timing of each stressor largely limit our understanding of biological responses to environmental change. In particular, early response to unpredictable environmental change, critical to survival and fitness in later life stages, is largely uncharacterized. Here, we characterize the early transcriptional response of the keystone species Daphnia magna to twelve environmental perturbations, including biotic and abiotic stressors. We first perform a differential expression analysis aimed at identifying differential regulation of individual genes in response to stress. This preliminary analysis revealed that a few individual genes were responsive to environmental perturbations and they were modulated in a stressor and genotype‐specific manner. Given the limited number of differentially regulated genes, we were unable to identify pathways involved in stress response. Hence, to gain a better understanding of the genetic and functional foundation of tolerance to multiple environmental stressors, we leveraged the correlative nature of networks and performed a weighted gene co‐expression network analysis. We discovered that approximately one‐third of the Daphnia genes, enriched for metabolism, cell signalling and general stress response, drives transcriptional early response to environmental stress and it is shared among genetic backgrounds. This initial response is followed by a genotype‐ and/or condition‐specific transcriptional response with a strong genotype‐by‐environment interaction. Intriguingly, genotype‐ and condition‐specific transcriptional response is found in genes not conserved beyond crustaceans, suggesting niche‐specific adaptation.

Environmental DNA metabarcoding: Transforming how we survey animal and plant communities - Kristy Deiner; Holly M. Bik; Elvira Mächler; Mathew Seymour; Anaïs Lacoursière‐Roussel; Florian Altermatt; Simon Creer; Iliana Bista; David M. Lodge; Natasha de Vere; Michael E. Pfrender; Louis Bernatchez (Molecular Ecology, 2017)
The genomic revolution has fundamentally changed how we survey biodiversity on earth. High‐throughput sequencing (“ HTS ”) platforms now enable the rapid sequencing of DNA from diverse kinds of environmental samples (termed “environmental DNA ” or “ eDNA ”). Coupling HTS with our ability to associate sequences from eDNA with a taxonomic name is called “ eDNA metabarcoding” and offers a powerful molecular tool capable of noninvasively surveying species richness from many ecosystems. Here, we review the use of eDNA metabarcoding for surveying animal and plant richness, and the challenges in using eDNA approaches to estimate relative abundance. We highlight eDNA applications in freshwater, marine and terrestrial environments, and in this broad context, we distill what is known about the ability of different eDNA sample types to approximate richness in space and across time. We provide guiding questions for study design and discuss the eDNA metabarcoding workflow with a focus on primers and library preparation methods. We additionally discuss important criteria for consideration of bioinformatic filtering of data sets, with recommendations for increasing transparency. Finally, looking to the future, we discuss emerging applications of eDNA metabarcoding in ecology, conservation, invasion biology, biomonitoring, and how eDNA metabarcoding can empower citizen science and biodiversity education.

Reproductive isolation and environmental adaptation shape the phylogeography of mountain pine beetle ( Dendroctonus ponderosae ) - Eddy J. Dowle; Ryan R. Bracewell; Michael E. Pfrender; Karen E. Mock; Barbara J. Bentz; Gregory J. Ragland (Molecular Ecology, 2017)
Chromosomal rearrangement can be an important mechanism driving population differentiation and incipient speciation. In the mountain pine beetle ( MPB , Dendroctonus ponderosae ), deletions on the Y chromosome that are polymorphic among populations are associated with reproductive incompatibility. Here, we used RAD sequencing across the entire MPB range in western North America to reveal the extent of the phylogeographic differences between Y haplotypes compared to autosomal and X‐linked loci. Clustering and geneflow analyses revealed three distinct Y haplogroups geographically positioned within and on either side of the Great Basin Desert. Despite close geographic proximity between populations on the boundaries of each Y haplogroup, there was extremely low Y haplogroup mixing among populations, and gene flow on the autosomes was reduced across Y haplogroup boundaries. These results are consistent with a previous study suggesting that independent degradation of a recently evolved neo‐Y chromosome in previously isolated populations causes male sterility or inviability among Y haplotype lineages. Phylogeographic results supported historic contraction of MPB into three separate Pleistocene glacial refugia followed by postglacial range expansion and secondary contact. Distinct sets of SNP s were statistically associated with environmental data among the most genetically distinct sets of geographic populations. This finding suggests that the process of adaptation to local climatic conditions is influenced by population genetic structure, with evidence for largely independent evolution in the most genetically isolated Y haplogroup.

Patterns of divergence across the geographic and genomic landscape of a butterfly hybrid zone associated with a climatic gradient - Sean F. Ryan; Michael C. Fontaine; J. Mark Scriber; Michael E. Pfrender; Shawn T. O'Neil; Jessica J. Hellmann (Molecular Ecology, 2017)
Hybrid zones are a valuable tool for studying the process of speciation and for identifying the genomic regions undergoing divergence and the ecological (extrinsic) and nonecological (intrinsic) factors involved. Here, we explored the genomic and geographic landscape of divergence in a hybrid zone between Papilio glaucus and Papilio canadensis . Using a genome scan of 28,417 dd RAD SNP s, we identified genomic regions under possible selection and examined their distribution in the context of previously identified candidate genes for ecological adaptations. We showed that differentiation was genomewide, including multiple candidate genes for ecological adaptations, particularly those involved in seasonal adaptation and host plant detoxification. The Z chromosome and four autosomes showed a disproportionate amount of differentiation, suggesting genes on these chromosomes play a potential role in reproductive isolation. Cline analyses of significantly differentiated genomic SNP s, and of species‐diagnostic genetic markers, showed a high degree of geographic coincidence (81%) and concordance (80%) and were associated with the geographic distribution of a climate‐mediated developmental threshold (length of the growing season). A relatively large proportion (1.3%) of the outliers for divergent selection were not associated with candidate genes for ecological adaptations and may reflect the presence of previously unrecognized intrinsic barriers between these species. These results suggest that exogenous (climate‐mediated) and endogenous (unknown) clines may have become coupled and act together to reinforce reproductive isolation. This approach of assessing divergence across both the genomic and geographic landscape can provide insight about the interplay between the genetic architecture of reproductive isolation and endogenous and exogenous selection.

Temporal genetic stability in natural populations of the waterflea D aphnia magna in response to strong selection pressure - Luisa Orsini; Hollie Marshall; Maria Cuenca Cambronero; Anurag Chaturvedi; Kelley W. Thomas; Michael E. Pfrender; Katina I. Spanier; Luc De Meester (Molecular Ecology, 2016)
Studies monitoring changes in genetic diversity and composition through time allow a unique understanding of evolutionary dynamics and persistence of natural populations. However, such studies are often limited to species with short generation times that can be propagated in the laboratory or few exceptional cases in the wild. Species that produce dormant stages provide powerful models for the reconstruction of evolutionary dynamics in the natural environment. A remaining open question is to what extent dormant egg banks are an unbiased representation of populations and hence of the species’ evolutionary potential, especially in the presence of strong environmental selection. We address this key question using the water flea Daphnia magna , which produces dormant stages that accumulate in biological archives over time. We assess temporal genetic stability in three biological archives, previously used in resurrection ecology studies showing adaptive evolutionary responses to rapid environmental change. We show that neutral genetic diversity does not decline with the age of the population and it is maintained in the presence of strong selection. In addition, by comparing temporal genetic stability in hatched and unhatched populations from the same biological archive, we show that dormant egg banks can be consulted to obtain a reliable measure of genetic diversity over time, at least in the multidecadal time frame studied here. The stability of neutral genetic diversity through time is likely mediated by the buffering effect of the resting egg bank.

Conserved transcriptional responses to cyanobacterial stressors are mediated by alternate regulation of paralogous genes in Daphnia - Jana Asselman; Michael E. Pfrender; Jacqueline A. Lopez; Dieter I. M. De Coninck; Colin R. Janssen; Joseph R. Shaw; Karel A. C. De Schamphelaere (Molecular Ecology, 2015)
Despite a significant increase in genomic data, our knowledge of gene functions and their transcriptional responses to environmental stimuli remains limited. Here, we use the model keystone species Daphnia pulex to study environmental responses of genes in the context of their gene family history to better understand the relationship between genome structure and gene function in response to environmental stimuli. Daphnia were exposed to five different treatments, each consisting of a diet supplemented with one of five cyanobacterial species, and a control treatment consisting of a diet of only green algae. Differential gene expression profiles of Daphnia exposed to each of these five cyanobacterial species showed that genes with known functions are more likely to be shared by different expression profiles, whereas genes specific to the lineage of Daphnia are more likely to be unique to a given expression profile. Furthermore, while only a small number of nonlineage‐specific genes were conserved across treatment type, there was a high degree of overlap in expression profiles at the functional level. The conservation of functional responses across the different cyanobacterial treatments can be attributed to the treatment‐specific expression of different paralogous genes within the same gene family. Comparison with available gene expression data in the literature suggests differences in nutritional composition in diets with cyanobacterial species compared to diets of green algae as a primary driver for cyanobacterial effects on Daphnia . We conclude that conserved functional responses in Daphnia across different cyanobacterial treatments are mediated through alternate regulation of paralogous gene families.

The evolution of salinity tolerance in Daphnia : a functional genomics approach - Leigh C. Latta; Lawrence J. Weider; John K. Colbourne; Michael E. Pfrender (Ecology Letters, 2012)
One route to genetic adaptation in a novel environment is the evolution of ecological generalisation. Yet, identifying the cost that a generalist pays for the increased breadth of tolerance has proven elusive. We integrate phenotypic assays with functional genomics to understand how tolerance to a salinity gradient evolves, and we test the relationship between the fitness cost of this generalisation and the cost of transcription that arises from evolved differences in patterns of gene expression. Our results suggest that a salt‐tolerant genotype of Daphnia is characterised by constitutively expressed genes, which does not incur a loss of fitness or a cost of transcription relative to a salt‐intolerant genotype in low saline environments. We find that many genes whose expression pattern evolved in response to salinity are also involved in the response to predators, suggesting that the cost of generalisation may be due to trade‐offs along other environmental axes.

Conservation in a cup of water: estimating biodiversity and population abundance from environmental DNA - DAVID M. LODGE; CAMERON R. TURNER; CHRISTOPHER L. JERDE; MATTHEW A. BARNES; LINDSAY CHADDERTON; SCOTT P. EGAN; JEFFREY L. FEDER; ANDREW R. MAHON; MICHAEL E. PFRENDER (Molecular Ecology, 2012)
Three mantras often guide species and ecosystem management: (i) for preventing invasions by harmful species, ‘early detection and rapid response’; (ii) for conserving imperilled native species, ‘protection of biodiversity hotspots’; and (iii) for assessing biosecurity risk, ‘an ounce of prevention equals a pound of cure.’ However, these and other management goals are elusive when traditional sampling tools (e.g. netting, traps, electrofishing, visual surveys) have poor detection limits, are too slow or are not feasible. One visionary solution is to use an organism’s DNA in the environment (eDNA), rather than the organism itself, as the target of detection. In this issue of Molecular Ecology , Thomsen et al. (2012) provide new evidence demonstrating the feasibility of this approach, showing that eDNA is an accurate indicator of the presence of an impressively diverse set of six aquatic or amphibious taxa including invertebrates, amphibians, a fish and a mammal in a wide range of freshwater habitats. They are also the first to demonstrate that the abundance of eDNA, as measured by qPCR, correlates positively with population abundance estimated with traditional tools. Finally, Thomsen et al. (2012) demonstrate that next‐generation sequencing of eDNA can quantify species richness. Overall, Thomsen et al. (2012) provide a revolutionary roadmap for using eDNA for detection of species, estimates of relative abundance and quantification of biodiversity.

Genetic architecture and phenotypic plasticity of thermally-regulated traits in an eruptive species, Dendroctonus ponderosae - Barbara J. Bentz; Ryan R. Bracewell; Karen E. Mock; Michael E. Pfrender (Evolutionary Ecology, 2011)

Species and genotype diversity drive community and ecosystem properties in experimental microcosms - Leigh C. Latta; Michelle Baker; Todd Crowl; J. Jacob Parnell; Bart Weimer; Daryll B. DeWald; Michael E. Pfrender (Evolutionary Ecology, 2011)

Genetic resilience of Daphnia populations following experimental removal of introduced fish - Leigh C. Latta; Debra L. Fisk; Roland A. Knapp; Michael E. Pfrender (Conservation Genetics, 2010)

Plant genotypic diversity and environmental stress interact to negatively affect arthropod community diversity - Megan K. Kanaga; Leigh C. Latta; Karen E. Mock; Ronald J. Ryel; Richard L. Lindroth; Michael E. Pfrender (Arthropod-Plant Interactions, 2009)

Biodiversity in microbial communities: system scale patterns and mechanisms - J. JACOB PARNELL; TODD A. CROWL; BART C. WEIMER; MICHAEL E. PFRENDER (Molecular Ecology, 2009)
The relationship between anthropogenic impact and the maintenance of biodiversity is a fundamental question in ecology. The emphasis on the organizational level of biodiversity responsible for ecosystem processes is shifting from a species‐centred focus to include genotypic diversity. The relationship between biodiversity measures at these two scales remains largely unknown. By stratifying anthropogenic effects between scales of biodiversity of bacterial communities, we show a statistically significant difference in diversity based on taxonomic scale. Communities with intermediate species richness show high genotypic diversity while speciose and species‐poor communities do not. We propose that in species‐poor communities, generally comprising stable yet harsh conditions, physiological tolerance and competitive trade‐offs limit both the number of species that occur and the loss of genotypes due to decreases in already constrained fitness. In species‐rich communities, natural environmental conditions result in well‐defined community structure and resource partitioning. Disturbance of these communities disrupts niche space, resulting in lower genotypic diversity despite the maintenance of species diversity. Our work provides a model to inform future research about relationships between species and genotypic biodiversity based on determining the biodiversity consequences of changing environmental context.

The adaptive landscape as a conceptual bridge between micro- and macroevolution - Stevan J. Arnold; Michael E. Pfrender; Adam G. Jones (Genetica, 2001)

Lack of concordance between genetic diversity estimates at the molecular and quantitative-trait levels - Michael E. Pfrender; Ken Spitze; Justin Hicks; Kendall Morgan; Leigh Latta; Michael Lynch (Conservation Genetics, 2000)